2004
DOI: 10.1097/01.asn.0000116241.47678.49
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine for the Prevention of Radiocontrast Induced Nephropathy

Abstract: Abstract. N-acetylcysteine has been recommended for patients with renal insufficiency who are to receive radiocontrast media. However, trials of oral N-acetylcysteine for the prevention of radiocontrast-induced nephropathy have yielded inconsistent results. A systematic review of patient and study characteristics was undertaken to discover possible explanations of the inconsistencies. The databases MEDLINE, EMBASE, and CENTRAL (1966 to March 2003) were searched in all languages, and conference proceedings fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(104 citation statements)
references
References 46 publications
3
96
2
3
Order By: Relevance
“…Interestingly, in animal studies, both intravenous contrast dye 37,38 and highdose vancomycin 15,16 have been demonstrated to promote free radical formation within renal tissue, which is hypothesized to cause tubular damage primarily through vascular endothelial dysfunction, vasoconstriction, and subsequent reperfusion injury. N-acetylcysteine is frequently administered to patients about to receive intravenous contrast dye (although its benefit remains controversial 37,39 ); N-acetylcysteine has also been shown in an animal model to attenuate vancomycin-induced renal injury. 40 Receipt of concomitant aminoglycosides was not significantly associated with nephrotoxicity, in contrast with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in animal studies, both intravenous contrast dye 37,38 and highdose vancomycin 15,16 have been demonstrated to promote free radical formation within renal tissue, which is hypothesized to cause tubular damage primarily through vascular endothelial dysfunction, vasoconstriction, and subsequent reperfusion injury. N-acetylcysteine is frequently administered to patients about to receive intravenous contrast dye (although its benefit remains controversial 37,39 ); N-acetylcysteine has also been shown in an animal model to attenuate vancomycin-induced renal injury. 40 Receipt of concomitant aminoglycosides was not significantly associated with nephrotoxicity, in contrast with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…La Tabella 1 è stata derivata da uno studio eseguito per la somministrazione intra-arteriosa di MdC [14], in cui si è usata una metodica di calcolo semiquantitativo del rischio da MdC. Il fatto che il rischio di nefropatia da MdC può essere più alto in caso the procedure [18]. The usefulness of N-acetylcysteine in preventing contrast-induced nephropathy [19] is still being debated in the literature; however, until conclusive evidence becomes available, we believe it reasonable to continue its use, as it is inexpensive, simple to administer and free of side effects.…”
Section: In Media Il 20% Dei Pazienti Prenotati Per Un Esame Con MDC unclassified
“…The usefulness of N-acetylcysteine in preventing contrast-induced nephropathy [19] is still being debated in the literature; however, until conclusive evidence becomes available, we believe it reasonable to continue its use, as it is inexpensive, simple to administer and free of side effects. If necessary, the nephrologist requests serum creatinine testing after the examination (at 12, 24, 36 or 48 di somministrazione intra-arteriosa del mezzo di contrasto [15] [18]. In letteratura l'utilità dell'acetilcisteina per la prevenzione della nefropatia da MdC è assai controverso [19] h); a 25% increase in serum creatinine within 3 days after contrast administration is considered to be contrast-induced nephropathy [20].…”
Section: In Media Il 20% Dei Pazienti Prenotati Per Un Esame Con MDC mentioning
confidence: 99%
“…If PD patients must undergo a radiocontrast study, they should be well hydrated (although, obviously not excessively so) and the lowest volume of an iso-osmotic or low-osmotic contrast agent should be used. The use of N-acetylcysteine to prevent contrast-induced nephropathy is controversial and there are very few studies evaluating its use in the dialysis population (31). Nonsteroidal anti-inflammatory drugs should be avoided in PD patients with preserved RRF.…”
Section: Other Factorsmentioning
confidence: 99%